THE EFFECT OF USING READ PAIR SHARE (RPS) STRATEGY IN READING DESCRIPTIVE TEXT MASTERY AT THE GRADE VIII OF SMP NEGERI 1 SIPIROK - Siagian, Abdul Rahman (Linguistik : Jurnal Bahasa dan Sastra, 2022)
The research was conducted by the researcher at the Grade VIII SMP Negeri 1 Sipirok. The aims of this research was to find out if there a significant effect of using Read Pair Share (RPS) strategy in reading descriptive text. In order to achieve the purpose of this research, the writer carried out in quantitative method by applying experimental types. The population of this research was the Grade VIII SMP Negeri 1 Sipirok. They were 64 students, the researcher used total sampling technique to get the sample. The samples were 32 students. Reading descriptive text was applied as the instrument of this research, the writer used â€œtâ€ tes formula. Based on the data that has been analyzed, it can be found that (1) the studentsâ€™ achievement in reading descriptive text without using Read Pair Share (RPS) strategy was â€œenoughâ€ (66.8), (2) their value byÂ  using Read Pair Share (RPS) strategy can be categorized â€œgoodâ€ (72.8), and (3) there was a significant effect the result of reading descriptive by using Read Pair Share (RPS) strategy. It meant that the hypothesis was accepted.Â